(untitled) (Boston, 2013)
Selling Today: Partnering to Create Value helps students understand the value of developing their personal selling skills by exposing them to a careful integration of personal selling academic theory and real-world applications. And with the largest number of “learn by doing” materials available in any personal selling text, Manning/Ahearne/Reece offers instructors a variety of teaching tools to strengthen the learning process. As the developed nations of the world transition from a production focus to a sales-and-service focus, this cutting-edge new edition prepares students to succeed as members of a new generation of businesspeople.
Keywords: Sự bán hàng,Selling